Balancing ethical norms and duties for the introduction of new medicines through conditional marketing authorization: a research agenda - Maksimova, Mariia V.; van Thiel, Ghislaine J. M. W.; Tromp, Yke; Lechner, Rosan; van Delden, Johannes J. M.; Bloem, Lourens T. (Frontiers in Medicine, 2024)
The European Medicines Agency’s conditional marketing authorization (CMA) aims to expedite patient access to medicines for unmet medical needs by shifting a part of the drug development process post-authorization. We highlight ethical issues surrounding CMA, comprising (i) the complexity of defining unmet medical need; (ii) poor understanding of CMA and its impact on informed consent; (iii) hope versus unrealistic optimism; (iv) implications of prolonged post-authorization studies and potential patient harm; (v) rights and duties of patients surrounding participation in post-authorization studies; (vi) access to previously authorized CMA medicines; and (vii) the “benefit slippage” phenomenon, defined as the gradual shift of strict criteria to less strict criteria. We propose a comprehensive research agenda to address these ethical issues, and stress the need for multi-stakeholder engagement to ensure patient-centered use of CMA.